Speciation of copper in soils and relation with its concentration in fruits - Yaman, M (Marcel Dekker Inc, 2000)
Different extraction reagents were studied in soils and the results obtained were compared with copper (Cu) contents of seven type fruits grown in these soils. For fruits, wet and dry ashing methods were applied and acceptable results were obtained by using dry ashing. The speciation is based on the dissolution of the soil samples in KNO3/H2O2, oxalic acid, acetic acid, EDTA and citric acid as extraction reagents at hot and cold conditions. Mean total Cu concentrations for all fruits studied were (mg kg(-1)) in the range of 3.0-7.0 (dried weight basis). Significant positive correlations have been found between Cu contents of various fruits and different extractants studied. Flame atomic absorption spectrometry was used for determination of Cu in digestions. Probable chemical forms of Cu in soils were evaluated.
Keywords: Atomic-Absorption Spectrometry; Activated-Carbon Enrichment; Vegetables; Lead; Preconcentration; Manganese; Matrices; Cadmium